Nanostructured Materials for Visible Light Photocatalysis - Nayak, Arpan Kumar; Sahu, Niroj Kumar (Micro & nano technologies., 2022)
Nanostructured Materials for Visible Light Photocatalysis describes the various methods of synthesizing different classes of nanostructured materials that are used as photocatalysts for the degradation of organic hazardous dyes under visible light irradiation. The first three chapters include a general introduction, basic principles, mechanisms, and synthesis methods of nanomaterials for visible light photocatalysis. Recent advances in carbon, bismuth series, transition metal oxide and chalcogenides-based nanostructured materials for visible light photocatalysis are discussed. Later chapters describe the role of phosphides, nitrides, and rare earth-based nanostructured-based materials in visible light photocatalysis, as well as the characteristics, synthesis, and fabrication of photocatalysts. The role of doping, composites, defects, different facets, morphology of nanostructured materials and green technology for efficient dye removal under visible-light irradiation are also explored. Other topics covered include large-scale production of nanostructured materials, the challenges in present photocatalytic research, the future scope of nanostructured materials regarding environmental hazard remediation under visible light, and solar light harvesting. This book is a valuable reference to researchers and enables them to learn more about designing advanced nanostructured materials for wastewater treatment and visible-light irradiation.